“Autonomy is the Name of the Game:” Montessori Pedagogy [AND] Socioemotional Development - Jandrt, Jenna; Schultz, Nicole J. (My University, 2018)
Current literature regarding Montessori methods surrounds academic success in a variety of disciplines, but little suggests that students attending a Montessori school develop differently in regard to social and emotional development. The purpose of the current study was to investigate ways in which Montessori schools are designed in an intentional way to foster the socioemotional development of students and ways in which these practices are beneficial. Five components of socioemotional development (autonomy, conflict reconciliation, diversity, and empathy) were derived from a compilation of professional scales measuring socioemotional development. The results of research are significant in that they address topics that have to be fully explored which is the effects a Montessori education has on social and emotional development in youth. The implications of this research are applicable to parents with young children, teachers, policy makers, and professionals working in academic settings because they may have strong potential to position them to better understand pedagogical methods and practices that best serve a child's socioemotional development. Findings and results are contextualized utilizing the Ecological Systems Theory modified by Urie Bronfenbrenner.
Color poster with text and images.
Keywords: Ecological Systems Theory; Child development; Montessori Method of education; Posters